Effect of Clove Oil Concentration on the Characteristics Of Cassava Starch (Manihot utilissima) Edible Film : Edible film with addition of clove oil - Antoro, Adi Indra; Rahmayani, Irma (Jurnal Bio-Geo Material Dan Energi, 2022)
The purpose of this study was to determine the effect of clove oil concentration on the characteristics of edible film from cassava starch and to obtain the best clove oil concentration in inhibiting microbial growth on edible films. This research was conducted in 3 stages, namely cassava starch extraction, making edible films, and data analysis. This research was conducted using a completely randomized design (CRD) with 5 treatment of clove oil concentration and 4 replications to obtain 20 experimental units. The clove oil levels used was 0%, 0.4%, 0.8%, 1.2% and 1.6%. The results showed that the concentration of clove oil had an effect on thickness, transparency, compressive strength and was able to inhibit the growth of Staphylococcus aureus bacteria on edible films, but has no significant effect on the water vapor transmission rate (WVTR). Edible film with the addition of 1.6% concentration produces edible film with the best characteristics, namely 0.175 mm thickness, 7.053 %/mm transparency, 72.70 N/m2 compressive strength, water vapor transmission rate (WVTR) 21.00 g/m2.24hours, and able to inhibit the growth of Staphylococcus aureus bacteria with an inhibitory power of 13.82 mm.